SANTON DARI KULIT BATANG TUMBUHAN ASAM KANDIS (Garcinitz cowa) - Darwati Darwati; Anni Aoggraeoi"; Sri AdisumiwiZ (Jurnal Kimia Terapan Indonesia, 2012)
The genus Garcinia is known to be a rich source of oxygenated xanthone, prenylated xanthone, and polyisoprenylated benzophenones. Some of them exhibiting various biological activities such as antimycrobachterial,antioxidant, cytotoxic, and antimalaria activities. Garcinia cowa belonging to the Guttiferaefamily, in Indonesia this plant is locally named asamkandis In our continuing phytochemical investigation of Garcinia plants is found in Indonesia a xanthone cowanine compound has been isolated from the steam bark of Garctnia cowa. The structure of this compound has been determined base on spectroscopic data including uv, lR,J-D NMR, and these are comparedwith the literaturedata.Keywords: Garcinia cowa, xanthone, cowanine